Analisis Proksimat, Protein Larut Air, dan Protein Larut Garam pada Beberapa Jenis Ikan Air Tawar Sumatera Selatan - Oka Weniarti Gultom; Susi Lestari; Rodiana Nopianti (Universitas Sriwijaya, 2015)
The purpose of this study was to determine the water-soluble protein and salt-soluble protein in some species of fresh water fish indigenous South Sumatera. This research was conducted on September 2014 until October 2014. The results obtained in this study were analyzed by using descriptive methods. The parameters used are chemical analysis (water content, protein content, fat content, ash content), water-soluble protein and salt-soluble protein. Chemical characteristics of some of the fish used in this study is the water content for 78% catfish (Cryptopteru limpok), climbing gouramies78.13%, 77.47 catfish (Mystus nemurus), marble goby 77.76%, 77.28% snakeheads. Ash content for 3.32% catfish (Cryptopteru limpok), climbing gouramies 1.98%, 3.31% catfish (Mystus nemurus), marble goby 1.97%, 3.24% snakeheads. Protein content for 5.19 mg/g catfish (Cryptopteru limpok), climbing gouramies 9.06 mg/g, 5.33 mg/g catfish (Mystus nemurus), marble goby 5.95 mg/g, 5.36 mg/g snakeheads. Fat content for 2.36% catfish (Cryptopteru limpok), climbing gouramies 3.09%, 3.3% catfish (Mystus nemurus), marble goby 1.83%, 2.23% snakeheads. Water-soluble protein for 5.17 mg/g catfish (Cryptopteru limpok), climbing gouramies 6.46 mg/g, 6.63 mg/g catfish (Mystus nemurus), marble goby 6.7 mg/g, 5.53 mg/g snakeheads. Salt-soluble protein for 4.08 mg/g catfish (Cryptopteru limpok), climbing gouramies 3.40 mg/g, 4.38 mg/g catfish (Mystus nemurus), sleepers 3.50 mg/g, 3.65 mg/g snakeheads